Integrating Discovery Learning with Kahoot to Enhance Elementary Science Learning Outcomes: A Classroom Action Research Study - Faradilla Nur Itsnaini; Yun Ratna Lagandesa; Sisriawan Lapasere; Rizal Rizal; Ryan Andhika Pratama; Surahman Surahman (Journal of Innovation and Research in Primary Education, 2026)
Low science learning outcomes in elementary schools often result from traditional teacher-centered instruction that fails to actively engage students in the learning process. This study investigated the effectiveness of integrating the Discovery Learning model with Kahoot media to improve science learning outcomes among fourth-grade elementary students. Employing a classroom action research design following Kemmis and McTaggart's spiral model, this study involved 23 fourth-grade students at Al Khairaat Tondo Elementary School in Indonesia. Data were collected through learning achievement tests, structured observations of teacher and student activities, and implemented across two cycles during October-November 2025. The intervention yielded substantial improvements in learning outcomes. Mean scores increased from 45.86 (pre-test) to 66.86 (Cycle I) and 76.26 (Cycle II), while classical completion rates rose from 4.34% to 56.52% and ultimately 82.60%, exceeding the predetermined success threshold of 65%. Observation data demonstrated enhanced student engagement (82.35% to 93.33%) and improved teacher implementation quality (75% to 94.04%) across cycles. The integrated Discovery Learning and Kahoot approach significantly enhanced both cognitive achievement and student engagement in science education. The synergistic combination of constructivist inquiry-based pedagogy with game-based assessment effectively transformed learning experiences for students with initially low achievement levels.